2021
DOI: 10.1088/1361-6501/abf30b
|View full text |Cite
|
Sign up to set email alerts
|

An optimized stacked diagnosis structure for fault diagnosis of wind turbine planetary gearbox

Abstract: Fault diagnosis of the planetary gearbox (PGB) of wind turbines (WTs) plays an important role in the normal operation of WTs. Current studies commonly focus on the diagnosis of fault types of WT PGBs. Nevertheless, in addition to identifying the fault type, the current severity of the fault is also instructive for the maintenance and repair of WT PGBs. Thus, a novel optimized stacked diagnosis structure (OSDS) is proposed for the identification of fault type and severity. Compressed sensing is adopted to imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
(47 reference statements)
0
20
0
Order By: Relevance
“…The gearbox dataset of Case 1 is provided by the University of Connecticut (UoC), 39,40 which has been extensively used to explore the performance of fault diagnosis methods. [41][42][43][44][45][46][47][48] In addition, Zhao et al 41 tested seven publicly available datasets through four benchmark types of deep learning models and showed that the UoC gearbox dataset is the most difficult to diagnose among the seven datasets. The gearbox data of Case 1 is used to study the universality and progressiveness of the proposed method.…”
Section: Case Studymentioning
confidence: 99%
“…The gearbox dataset of Case 1 is provided by the University of Connecticut (UoC), 39,40 which has been extensively used to explore the performance of fault diagnosis methods. [41][42][43][44][45][46][47][48] In addition, Zhao et al 41 tested seven publicly available datasets through four benchmark types of deep learning models and showed that the UoC gearbox dataset is the most difficult to diagnose among the seven datasets. The gearbox data of Case 1 is used to study the universality and progressiveness of the proposed method.…”
Section: Case Studymentioning
confidence: 99%
“…Fault diagnosis methods mainly include vibration signalbased methods [6][7][8][9] and thermal signal-based methods [10,11]. The vibration signal has high accuracy, it is the most accessible signal in research and applications.…”
Section: Introductionmentioning
confidence: 99%
“…The precision rate, recall rate, and F-score of this run are shown in figure12. In fault diagnosis, precision rate and recall rate are evaluation metrics, represented respectively as follows: Precision = TP/(TP + FP)(6) Recall = TP/(TP + FN)(7)…”
mentioning
confidence: 99%
“…In the past decades, rotating machines have been widely applied in modern industries [1]. Machinery failures during operations severely compromise safety and lead to large maintenance costs [2,3]. Effective and accurate machine health condition monitoring and fault diagnosis have always been in high demand.…”
Section: Introductionmentioning
confidence: 99%